Factors affecting heating of calzones in microwaves - Cullen, Lorri Denise (Kansas State University, 2010)
Determining the optimum cooking instructions for microwavable not-ready-to-eat foods requires an understanding of the factors that affect heating of foods in microwaves. Factors are often studied without consideration of interactions. Consumer-driven factors appear to be the least-studied. Microwave appliance, heat time, flip step, and plate material were studied to determine their effect on final temperature of a frozen hand-held calzone sandwich after heating. Initial studies to ensure wattage stability during testing and a study to narrow down the plates to be tested were also executed. In the central experiment, a calzone was heated on a microwavable plate for one minute, then flipped or not flipped and heated again for the remaining time in each of four microwave ovens. The microwave ovens differed in age and manufacturer, but were of similar stated wattage. Probes were attached to a data logger and temperatures were recorded every 5 seconds for 2 minutes post-heating to attain the average maximum temperature and lowest maximum temperature for each run. The data was evaluated by analysis of variance and significant differences were compared using Tukey means. All factors had significant effects on average maximum temperature and lowest maximum temperature with the exception of the flip step (p< .05). Plate type was the most critical factor. Calzones heated on paper plates were significantly hotter than those on stoneware plates (p<.05). Significant differences were also observed among microwaves and heat times (p<.05). An interaction between microwave and plate type indicated the effect of plate type was not consistent across all microwaves (p<.05). Although flip step, as tested, was not a significant factor, a follow-up experiment to de-couple the effect of the physical flipping of the calzone and the stopping of the microwave during the heating process indicated that the stopping of the microwave was more critical to heating than the actual flip step. A follow-up study of plate type, microwave and heat time in higher-wattage microwaves showed that microwave appliance and heat time again had significant effects on temperature (p<.05), however; plate type was not a significant factor in the higher-wattage microwaves. The effect of plate type was dependent on the exact microwave used. Various plate types and multiple microwaves in each wattage range should be used for development of microwavable frozen calzones because wattage alone cannot predict performance and because of the interaction between microwave and plate type.
Keywords: Microwave heating; Food safety; Not-ready-to-eat foods; Cooking instructions; Agriculture, Food Science and Technology (0359)